Fall Panicum: Biology and Control in Sugarcane - D. Calvin Odero; Brent Sellers; Les Baucum; Curtis Rainbolt (EDIS, 2011)
Fall panicum (Panicum dichotomiflorum) is a native grass that can be found throughout the United States in agronomic and horticultural crops, turfgrass, nurseries, landscapes, and noncrop areas. It grows well in warm wet conditions and is one of the most common grass weeds found in Florida sugarcane. This 3-page fact sheet provides sugarcane growers with guidance on its identification and control. Written by D.C. Odero, Brent Sellers, Les Baucum, and Curtis Rainbolt, and published by the UF Department of Agronomy, May 2011.